Hurricane force - DeLeon, Jana (DeLeon, Jana. Miss Fortune series., 2015)
"A force to be reckoned with...During missions as a CIA assassin, Fortune Redding saw and overcame most every obstacle, but Sinful, Louisiana, keeps producing new challenges for her. When a hurricane blows through, it brings a shower of counterfeit money raining down on the tiny bayou town.When the money is linked back to Ahmad, the arms dealer who issued the kill order on Fortune, everyone is worried that her nemesis is far too close for comfort. When Ahmad's men turn up in Sinful, the situation becomes life-and-death for Fortune, Ida Belle, and Gertie, and Deputy Carter LeBlanc learns Fortune's true identity. As Swamp Team 3 rushes to locate the counterfeiter, Fortune hopes to take down Ahmad and free herself from her fake life. But will her relationship with Carter make it now that he knows the truth?"--Back cover.